Evaluating the Implementation of Government Regulation No. 22 of 2021 on Environmental Protection and Management: A Study of AMDAL Compliance in Sand Mining - Nanda Sholihatunnisa; Abu Nawas; Muh Nasir (BULETIN ADALAH, 2026)
Poorly managed sand mining activities can lead to environmental degradation, including land degradation, water pollution, and ecosystem disruption. Government Regulation No. 22 of 2021 mandates the preparation of Environmental Impact Assessments (AMDAL) as part of environmental protection and management. This study aims to examine the implementation of this regulation, particularly the AMDAL requirement in sand mining activities in Pancanegara Village, Pabuaran District, Serang Regency. It also analyzes the positive and negative impacts of such activities on the local community. This research employs an empirical juridical method, combining a statutory and field approach. Data were collected through literature review and field research and analyzed qualitatively. The findings reveal that the implementation of the AMDAL requirement under Government Regulation No. 22 of 2021 has not been optimal. Contributing factors include limited supervision by authorities, low awareness among business actors, and administrative challenges in the licensing process. While sand mining contributes to local economic development, it also results in environmental damage, pollution, and social changes within the community. Keywords: Government Regulation No. 22 of 2021, AMDAL, sand mining, environmental protection, law enforcement.